Pengaruh Gaya Hidup, Suasana Toko dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Masa Pandemi Covid-19 di @Adakopi Parung Bogor - Wibisono, Satrio; Ilyas, Amin; Bahri, Khotimi (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine a new culture that develops towards increased coffee consumption every year, whether there are lifestyle factors, shop atmosphere and service quality on purchasing decisions at @AdaKopi Parung Bogor. The research method used is a quantitative type with descriptive nature with multiple linear analysis, with purposive sampling technique. Quantitative analysis includes validity and reliability tests, basic assumption tests, classical assumption tests, and hypothesis testing using the f and t test as well as the coefficient of determination (R2) analysis test and then distributing questionnaires to 383 @AdaKopi Parung Bogor consumers. Distribution of questionnaires using a 5-scale Likert scale with research testing using the SPSS 25 instrument test. The results are (H1) lifestyle towards purchasing decisions of tvalue 4.296> t table 1.966 H0 rejected Ha accepted. (H2) store atmosphere on purchasing decisions of tvalue 5.831> t table 1.966 H0 rejected Ha accepted. (H3) Service quality on purchasing decisions is tvalue 9,025> t table 1,966 H0 rejected Ha accepted. (H4) together, the size of the contribution of lifestyle, shop atmosphere and service quality to purchasing decisions is F value 342.505> F table 2.63 H0 is rejected Ha is accepted, it means that lifestyle, shop atmosphere and service quality jointly affect the purchase decision products at @AdaKopi Parung Bogor